Using Numerical Reservoir Simulation to Assess CO2 Capture and Underground Storage, Case Study on a Romanian Power Plant and Its Surrounding Hydrocarbon Reservoirs - Liviu Nicolae Dumitrache; Silvian Suditu; Iuliana Ghețiu; Ion Pană; Gheorghe Brănoiu; Cristian Eparu (Processes, 2023)
During current times, it is acknowledged that there is the often presence of extreme meteorological phenomena including floods and landslides, due to heavy rains, large wildfires, due to heat or droughts, permafrost melting, etc. At this stage, the world admits that anthropic activities have an important impact on these phenomena and considers that greenhouse gases are at the core of this climate change. The most common greenhouse gasses have general formulae COX and/or NOX, and they are released during different energy generating/conversion processes such as electric energy generation from fossil fuels or mechanical energy obtained from by-products of fossil fuels. Once acknowledged, the world’s countries have developed long-term strategies to eliminate gradually the release of these gases directly into Earth’s atmosphere. E.g., the EU aims to be climate-neutral by 2050; i.e., its economy will have net-zero greenhouse gas emissions. For this to happen, different effective methodologies have been drafted and implemented with underground gas storage in hydrocarbon depleted geological formations and/or saline aquifers being ones of significance when it comes to electric energy generation from fossil fuels in controlled spaces. The paper presents the simulation of capturing and injecting of these greenhouse gases through injection wells in neighboring depleted natural gas reservoirs using commercial numerical simulators for the Iernut natural gas (CH4) burning power plant which is one of Romania’s most important gas plants. Within this simulation study, the total CO2 quantity that can be stored via the proposed carbon capture and sequestration study and the proportion of each of the three CO2 storage mechanisms involved in the process (physical trapping, hydrodynamic trapping, and geochemical trapping) were determined and presented. Even though previous local studies investigated the potential of CO2 storage and sequestration into the Romanian underground reservoirs, none of it considered using the depleted ...